Identifikasi Asam Lemak dari Minyak Biji Alpukat (Persea americana Mill.) dan Uji Antibakteri terhadap Staphylococcus aureus - Wardah Fitria Tanjung; Reh Malem br Karo; Windi Wildani; Afri Abdiansyah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
The cause of infectious diseases that often occur in humans can be caused by pathogenic bacteria such as Staphylococcus aureus. The high rate of resistance caused by Staphylococcus aureus makes scientists continue to try to find secondary metabolites for safe medicinal ingredients. This study aims to identify fatty acids and determine the potential of avocado seed oil (BA) against Staphylococcus aureus. This type of research is a laboratory experimental research. The identification of fatty acids that make up BA oil is carried out by gas chromatography (GC) analysis, resulting in several free fatty acids (ALB) in the identified BA oil, such as saturated fatty acids and unsaturated fatty acids. The highest percent of three ALB components of BA oil were found in linoleic acid (26.182%), oleic acid (17.05%), and palmitic acid (12.21%). While the antibacterial activity test was carried out using the disc diffusion method, the variations in the concentration of BA oil used were 25%, 50%, 75%, and 100% with dimethyl sufoxide as K(-) and ciprofloxacin as K(+). Based on the antibacterial activity test, it is known that BA oil can inhibit the growth of Staphylococcus aureus bacteria with a weak category of <10 mm.